Preparedness to self-employed careers: development, validity, and reliability of an inventory for nursing students. (July 2022) - Rocco, Domenico; Caruso, Rosario; Magon, Arianna; Stievano, Alessandro
Abstract: Aims: To develop and psychometrically validate an inventory based on two scales: awareness regarding factors for determining the prices of freelance activities and knowledge regarding freelance-related norms among nursing undergraduate students in Italy. Background: Although self-employed nursing careers are strategic to enhance employability, no valid scales for assessing nursing students' preparedness to undertake self-employed careers are available. Design: A multi-method and multi-phase design were employed. Phase one encompassed developmental tasks for generating items and phase two included a cross-sectional data collection for determining the psychometric proprieties of the developed scales and their reliability. Results: The final inventory encompassed two scales showing adequate validity and reliability after testing it on 882 Italian undergraduate nursing students. The first scale, factors for determining the prices of activities, is based on care complexity and logistic characteristic (two-factor structure). The second scale, knowledge regarding freelance-related characteristics, encompassed two domains: knowledge regarding administrative rules and pensions and retirement issues. Conclusions: The developed inventory showed adequate evidence of initial validity and reliability, useful for filling the gap given by the unavailability of valid assessments for educators who pursue measuring the nursing students' preparedness to undertake self-employed careers.